(untitled) (PerCursos, 2025)
This text is the result of research on a political epistemology of development. Its objective is to understand the multiple theoretical and conceptual variables that constitute the terminology of development, arising from political economy and intertwined with practices and actions of a geopolitical, local and regional nature today. The article proposes a debate on the terminology of development based on the concepts and conceptions of utopia, ideology and neoliberalism. Its methodology is a bibliographic review, carried out by consulting, reading and analyzing books and scientific articles that are presented as relevant references for the debate. The final results of the research point to the ambivalence of discourses on development, which at certain times present themselves as utopia and, at others, as ideology. In both cases, it is essential to recognize the mobilizing force of social expectations inherent in discourses and proposals for development at the local and regional level, especially in the context of current neoliberal ideology